GDPR the Security Angle. (19th May 2018) - Edwards, Ian
Abstract: The General Data Protection Regulation (GDPR) is now upon us and mentions security a number of times, but what does this really mean for IT and security teams? Ian Edwards MBCS, Information Security Analyst at Markerstudy Group, takes a look in more detail.